(untitled) (Journal of Environmental Science and Natural Resources, 2016)
The study on Economics Faculty in using modern inputs against traditional inputs and practices for potato production were conducted in the different agro-ecological zones and agro-climatic locations of Bangladesh during 2011-2012. The aim of the study was how to enrich the knowledge of farmers and traders by the use of modern inputs (fertilizers, green pesticides and micronutrients) for potato production and management technologies. A total number of 150 farmers were randomly selected from Rangpur, Thakurgaon, and Comilla regions under agro-ecological zones of Tista Meander Floodplain, Old Himalayan Piedmont Plain and Middle Meghna River Floodplain respectively. Cobb-Douglas production function was used to measure the effect of various factors on potato production. The factors of production considered in this study were land preparation, labor cost, seed, fertilizer, pesticides, irrigation and land use cost. The cost was comparatively low in modern practices than higher in traditional practices as it was mainly due to adoption of recommended technology, appropriate dose and time in case of modern inputs and practices whereas non-recommended technology, higher dose of inputs adopted in traditional practices. The out-put in-terms of per unit yield was found 26 t ha-1 in modern practices but 24 t ha-1 in traditional practices. The net profit was significantly higher in modern practices than traditional practices; the net profit in modern practices was found at Rangpur Tk 98,079, Thakurgaon Tk 72, 741 and Comilla Tk 46, 950. It transpires from the study that the farmers would be economically benefitted if they use modern inputs; adopt technologies and practices in terms of using quality seed of improved varieties at recommended dose and time of use of fertilizers and pesticides, timely application of irrigation and appropriate crop management including weeding and other practices. J. Environ. Sci. & Natural Resources, 8(2): 83-87 2015